PENINGKATAN KEMAMPUAN BERPIKIR KREATIF SISWA KELAS VI MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) PADA MATERI HUBUNGAN ANTAR NEGARA DALAM MATA PELAJARAN IPAS DI UPTD SD INPRES OETETE 2 - Domi Lobo, Agustina; Moses Kopong Tokan; Adam Bol Nifu Benu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
21st-century education demands that students master 4C skills: critical thinking, creative thinking, communication, and collaboration. Creative thinking is essential for elementary students to generate new ideas, develop flexible solutions, and produce original works. However, preliminary observations at UPTD SD Inpres Oetete 2 revealed that Grade VI students had low creative thinking skills in the IPAS subject, specifically on the topic of International Relations. The average score was 67.2 with a classical completeness of only 38.7% from 31 students. Students were passive, their ideas were limited and uniform, and learning was dominated by teacher-centered lecture methods, which provided little room for creativity. This study aimed to improve students’ creative thinking skills through the implementation of the Project Based Learning model on the topic of International Relations. The research employed Classroom Action Research conducted in two cycles, following the Kemmis and McTaggart model. Each cycle consisted of planning, action, observation, and reflection stages. The subjects were 31 Grade VI students. Data were collected using teacher and student observation sheets, pretest-posttest written tests measuring fluency, flexibility, originality, and elaboration based on Torrance’s indicators, project product assessment sheets, and documentation. Data were analyzed using descriptive quantitative and qualitative techniques. The success indicator was set at a minimum of 80% of students achieving a score of ≥75 and classical completeness of ≥85%. The results showed significant improvement. The class average score increased from 67.2 in the pre-cycle to 73.6 in Cycle I and 87.4 in Cycle II. Classical completeness rose from 38.7% to 54.8% in Cycle I and reached 90.32% in Cycle II, exceeding the success indicator. Student activity improved from 71% in the Good category to 91.5% in the Very Good category. Among the four aspects of creative thinking, Originality and Elaboration showed the most substantial gains, increasing from 66.0% to 85.6% and from 74.8% to 88.2% respectively. The findings indicate that the Project Based Learning model effectively enhances creative thinking skills by providing students with opportunities to design, implement, and present projects actively and contextually. Therefore, it is recommended that teachers adopt PjBL in IPAS learning to foster 21st-century skills in elementary education, especially in schools with limited resources.